Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the equation [tex]\(\frac{1}{2} - x + \frac{3}{2} = x - 4\)[/tex] for [tex]\(x\)[/tex], follow these steps:
1. Combine like terms on the left-hand side of the equation:
The given equation is:
[tex]\[ \frac{1}{2} - x + \frac{3}{2} = x - 4 \][/tex]
Combine the constants [tex]\(\frac{1}{2}\)[/tex] and [tex]\(\frac{3}{2}\)[/tex]:
[tex]\[ \left(\frac{1}{2} + \frac{3}{2}\right) - x = x - 4 \][/tex]
Adding the fractions gives:
[tex]\[ \frac{4}{2} - x = x - 4 \][/tex]
Simplify [tex]\(\frac{4}{2}\)[/tex]:
[tex]\[ 2 - x = x - 4 \][/tex]
2. Move all terms involving [tex]\(x\)[/tex] to one side:
To isolate [tex]\(x\)[/tex], add [tex]\(x\)[/tex] to both sides of the equation:
[tex]\[ 2 - x + x = x - 4 + x \][/tex]
Simplify:
[tex]\[ 2 = 2x - 4 \][/tex]
3. Isolate [tex]\(2x\)[/tex]:
Add 4 to both sides to isolate the term with [tex]\(x\)[/tex]:
[tex]\[ 2 + 4 = 2x - 4 + 4 \][/tex]
Simplify:
[tex]\[ 6 = 2x \][/tex]
4. Solve for [tex]\(x\)[/tex]:
Divide both sides by 2:
[tex]\[ \frac{6}{2} = \frac{2x}{2} \][/tex]
Simplify:
[tex]\[ 3 = x \][/tex]
Therefore, the solution is [tex]\(x = 3\)[/tex].
Hence, the correct answer is:
C. [tex]\(x = 3\)[/tex]
1. Combine like terms on the left-hand side of the equation:
The given equation is:
[tex]\[ \frac{1}{2} - x + \frac{3}{2} = x - 4 \][/tex]
Combine the constants [tex]\(\frac{1}{2}\)[/tex] and [tex]\(\frac{3}{2}\)[/tex]:
[tex]\[ \left(\frac{1}{2} + \frac{3}{2}\right) - x = x - 4 \][/tex]
Adding the fractions gives:
[tex]\[ \frac{4}{2} - x = x - 4 \][/tex]
Simplify [tex]\(\frac{4}{2}\)[/tex]:
[tex]\[ 2 - x = x - 4 \][/tex]
2. Move all terms involving [tex]\(x\)[/tex] to one side:
To isolate [tex]\(x\)[/tex], add [tex]\(x\)[/tex] to both sides of the equation:
[tex]\[ 2 - x + x = x - 4 + x \][/tex]
Simplify:
[tex]\[ 2 = 2x - 4 \][/tex]
3. Isolate [tex]\(2x\)[/tex]:
Add 4 to both sides to isolate the term with [tex]\(x\)[/tex]:
[tex]\[ 2 + 4 = 2x - 4 + 4 \][/tex]
Simplify:
[tex]\[ 6 = 2x \][/tex]
4. Solve for [tex]\(x\)[/tex]:
Divide both sides by 2:
[tex]\[ \frac{6}{2} = \frac{2x}{2} \][/tex]
Simplify:
[tex]\[ 3 = x \][/tex]
Therefore, the solution is [tex]\(x = 3\)[/tex].
Hence, the correct answer is:
C. [tex]\(x = 3\)[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.